(untitled) (Journal of Current and Advance Medical Research, 2019)
Background: Primary Oral Squamous Cell Carcinoma can metastasize in the cervical lymph nodes. Objective: The purpose of the present study was to see the association of Anneroth’s scoring and frequency of cervical lymph node metastasis among primary oral squamous cell carcinoma patients. Methodology: This cross sectional study was conducted in the Department of Oral and Maxillofacial Surgery, Dhaka Dental College and Hospital, Dhaka, Bangladesh from November 2009 to December 2010 for a period of one year. Patients attending in the place of study with diagnosed case of oral squamous cell carcinoma were selected for the study after fulfilling the inclusion criteria. The resected primary lesion and neck lymph nodes were sent for histopathological examination. Histopathological grading of the primary lesion was done and neck lymphodes were graded as metastatic and non-metastatic. Results: This prospective study with 50 cases of oral squamous cell carcinoma was taken of which 28 cases were non-metastasis tumor. Each case was graded according to TNM classification, Broder’s grading and Anneroth’s classification. Both Anneroth’s classification (p=0.002) and Broder’s grading (p=0.017) were significant but Anneroth’s one was more significant than Broder’s. Conclusions: There is an association between Anneroth’s grading system with lymph node metastasis. Journal of Current and Advance Medical Research 2019;6(2): 69-72